2016
DOI: 10.1371/journal.pone.0169005
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Lipid Raft Function Increases Expression and Secretion of Monocyte Chemoattractant Protein-1 in 3T3-L1 Adipocytes

Abstract: The adipocyte is unique in its capacity to store lipids. In addition to triglycerides, the adipocyte stores a significant amount of cholesterol. Moreover, obese adipocytes are characterized by a redistribution of cholesterol with depleted cholesterol in the plasma membrane, suggesting that cholesterol perturbation may play a role in adipocyte dysfunction. We used methyl-β-cyclodextrin (MβCD), a molecule with high affinity for cholesterol, to rapidly deplete cholesterol level in differentiated 3T3-L1 adipocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 65 publications
0
14
0
1
Order By: Relevance
“…Moreover, it is also reported that lipid rafts facilitate virus replication. 57 Depletion of cholesterol, one of the main content of lipid rafts, significantly suppresses virus production. 58 This implies the importance of lipid in the development of virus infection and COVID-19.…”
Section: How Obesity Affects the Pathogenesis Of Covid-19mentioning
confidence: 99%
“…Moreover, it is also reported that lipid rafts facilitate virus replication. 57 Depletion of cholesterol, one of the main content of lipid rafts, significantly suppresses virus production. 58 This implies the importance of lipid in the development of virus infection and COVID-19.…”
Section: How Obesity Affects the Pathogenesis Of Covid-19mentioning
confidence: 99%
“…However, a link between cyclodextrins and iatrogenic hearing loss has been noted in several species, including humans [ 4 ]. In particular, methyl-β-cyclodextrin has been widely used for the selective removal of cholesterol and disruption of lipid rafts in different cell lines (see, e.g., [ 5 , 6 ]). The neurological risks of using methyl-β-cyclodextrin are informed by the reported toxicity of this compound to neuronal cell lines [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caveolae are small, flask-shaped invaginations in the plasma membrane composed of high levels of cholesterol and glycosphingolipids as well as the integral membrane protein caveolin(26). To determine whether SARS-CoV-2 enters cells through a caveolae-mediated pathway, we first treated cells with filipin or methyl-β-cyclodextrin (MβCD), both of which could disrupt the integrity of cholesterol-enriched membrane microdomains(27). Compared to control cells, uptake of cholera toxin subunit B (CTB), which has been reported to be internalized via caveolae-mediated endocytosis (2830), was blocked at cell surface when cells were treated with filipin or MβCD (Fig S2), suggesting these drugs can block caveolae-mediated endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…Caveolae are small, flask-shaped invaginations in the plasma membrane composed of high levels of cholesterol and glycosphingolipids as well as the integral membrane protein caveolin (26). To determine whether SARS-CoV-2 enters cells through a caveolaemediated pathway, we first treated cells with filipin or methyl--cyclodextrin (MCD), both of which could disrupt the integrity of cholesterol-enriched membrane microdomains (27).…”
Section: S Pseudovirus Infection Does Not Require Caveolae-mediated Ementioning
confidence: 99%